Fermented foods affect the seasonal stability of gut bacteria in an Indian rural population - Jeyaram, Kumaraswamy; Lahti, Leo; Tims, Sebastian; Heilig, Hans G. H. J.; van Gelder, Antonie H.; de Vos, Willem M.; Smidt, Hauke; Zoetendal, Erwin G. (Springer Science and Business Media LLC, 2025)
The effect of fermented foods on healthy human gut microbiota structure and function, particularly its seasonal preference and frequent long-term consumption, has been largely uncharacterised. Here, we assess the gut microbiota and metabolite composition of 78 healthy Indian agrarian individuals who differ in the intake of fermented milk and soybean products by seasonal sampling during hot-humid summer, autumn and dry winter. Here we show that, seasonal shifts between the Prevotella- and Bifidobacterium/Ruminococcus-driven community types, or ecological states, and associated fatty acid derivatives, with a bimodal change in Bacteroidota community structure during summer, particularly in fermented milk consumers. Our results associate long-term fermented food consumption with reduced gut microbiota diversity and bacterial load. We identify taxonomic groups that drive the seasonal fluctuation and associated shifts between the two ecological states in gut microbiota. This understanding may pave the way towards developing strategies to sustain a healthy and resilient gut microbiota through dietary interventions.